Pengembangan Scrapbook Sebagai Media Pembelajaran Fisika - Sari, Liawati Permata; Patimah, Siti; Yusandika, Ajo Dian (Indonesian Journal of Science and Mathematics Education, 2019)
Abstract: This study aims to determine the feasibility of learning media Scrapbook on Solar System materials, as well as to know the response of teachers and learners to the development of learning media Scrapbook on Solar System materia ls.This research is a type of research and development (R and D). The steps of research and development are guided by Brog and Gall model with seven stages. This research was conducted at UIN Raden Intan Lampung, SMPN 21 Bandar Lampung, SMPN 13 Bandar Lampung, and Mts Muhammadiyah Bandar Lampung. The instrument of data collection used is questionnaire or questionnaire. Technique of collecting data using questionnaire with Likert scale. Data analysis techniques used are qualitative descriptive analysis techniques and descriptive statistical analysis. Media feasibility results based on the assessment of media experts and material experts are included in very good criteria. As well as the outcomes of teacher and learner responses through small group trials and field trials were assessed with very good criteria. Scrapbook learning media on the material of the Solar System as a whole received an assessment that is included in the criteria very well, so it is worthy to be used as a medium of learning.Abstrak: Penelitian ini bertujuan untuk mengetahui kelayakan media pembelajaran Scrapbook pada materi Tata Surya, serta mengetahui respon guru dan peserta didik terhadap pengembangan media pembelajaran Scrapbook pada materi Tata Surya. Penelitian ini merupakan jenis penelitian dan pengembangan (R and D). Langkah-langkah penelitian dan pengembangan berpedoman pada model Brog and Gall dengan tujuh tahapan. Penelitian ini dilaksanakan di UIN Raden Intan Lampung, SMPN 21 Bandar Lampung, SMPN 13 Bandar Lampung, dan Mts Muhammadiyah Bandar Lampung. Instrumen pengumpulan data yang digunakan adalah angket atau kuesioner. Teknik pengumpulan data menggunakan angket dengan skala Likert. Teknik analisis data yang digunakan yaitu teknik analisis deskriptif kualitatif dan analisis statistik deskriptif. Hasil kelayakan media berdasarkan penilaian ahli media dan ahli materi termasuk dalam kriteria sangat baik. Serta hasil respon guru dan peserta didik melalui uji coba kelompok kecil dan uji coba lapangan memperoleh penilaian dengan kriteria sangat baik. Media  pembelajaran Scrapbook pada materi Tata Surya secara keseluruhan memperoleh penilaian yang termasuk dalam kriteria sangat baik, sehingga layak digunakan sebagai media pembelajaran.